Kebijakan Optimalisasi Tugas Dan Fungsi Intelijen Kepolisian Dalam Upaya Deteksi Dini Pencegahan Tindak Pidana Terorisme - M Fadli Ferdiansyah Putra; T. Erwinsyahbana; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The State Police of the Republic of Indonesia, hereinafter referred to as a government institution, has the main task of being regulated in Law No. 2 of 2002 concerning the Indonesian National Police. In accordance with Article 13 of Law No. 2 of 2002, the Police have the main task of maintaining public security and order, enforcing the law, and providing protection, protection and services to the community. The problem in this research is to analyze the role of police security intelligence in conducting early detection of terrorism prevention efforts in the jurisdiction of the Central Aceh Police, and to analyze the factors that hinder Police security intelligence in carrying out early detection of efforts to prevent terrorism crimes in the jurisdiction of the Aceh Police. Central, as well as analyzing how to optimize the duties and functions of Police Intelligence in early detection of the prevention of criminal acts of terrorism in the jurisdiction of the Central Aceh Police. Based on the results of the study, it was determined that the role of police intelligence in preventing criminal acts of terrorism was to carry out early detection in order to know all changes in social life in society and its further development, identify the nature of threats that are being and will be faced.